2019
DOI: 10.1029/2018ea000503
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evaluation of GPM‐IMERG Rainfall Estimates Over Three Distinct Climate Zones With APHRODITE

Abstract: Evaluation of Global Precipitation Measurement‐Integrated Multi‐satellitE Retrieval for GPM (GPM‐IMERG) final precipitation product is performed over Japan, Nepal, and Philippines regions against further improved APHRODITE‐2 V1801R1 product. The evolution is carried out for nearly two consecutive years 2014–2015. Various qualitative and quantitative statistical indices such as mean bias, root‐mean‐square error, correlation coefficient, false alarming ratio, and probability of detection are considered to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 36 publications
(40 reference statements)
1
39
0
Order By: Relevance
“…4b, 5, and 6 and Table 7). Xu et al (2017), Anjum et al (2018), Sunilkumar et al (2019), and Islam (2018) reported similar results over southern Tibetan Plateau, northern Pakistan, Japan and Nepal, and Bangladesh, respectively. This overestimation is higher for early and late runs compared to the final runs, especially for V06.…”
Section: (Iv) Gpcc Full Data Reanalysis and Gpcc Monitoringmentioning
confidence: 53%
“…4b, 5, and 6 and Table 7). Xu et al (2017), Anjum et al (2018), Sunilkumar et al (2019), and Islam (2018) reported similar results over southern Tibetan Plateau, northern Pakistan, Japan and Nepal, and Bangladesh, respectively. This overestimation is higher for early and late runs compared to the final runs, especially for V06.…”
Section: (Iv) Gpcc Full Data Reanalysis and Gpcc Monitoringmentioning
confidence: 53%
“…A study over multiple complex terrain regions found that GSMaP V07 was able to detect the orographic rainfall and the rainfall amounts and outperforms IMERG V06B in Nepal with evaluation against limited stations (Derin et al, 2019), whereas evaluation based on large‐scale station network revealed that GSMaP‐Gauge product was more consistent with reproducing spatial pattern while IMERG product was more reasonable to reproduce precipitation amount over the country (Sharma, Chen, et al, 2020). Similarly, Sunilkumar et al (2019) found that IMERG product was reliable to estimate rainfall amounts as that in APHRODITE over Asian countries, including Nepal. However, most of the abovementioned global as well as regional studies suggested for continuous evaluation of SBPP for complex topography—still needed to further advance the product algorithms (Chen & Li, 2016; Lu & Yong, 2018; Saber & Yilmaz, 2018; Wang & Yong, 2020; Wang, Zhang, & Zhang, 2019).…”
Section: Introductionmentioning
confidence: 88%
“…Then the interpolated precipitation at each station was In this study, the evaluations were conducted in three steps. In the first step, the performance of the three NWP models and SPEs in terms of capturing the spatial distribution of precipitation for the three flood events (17)(18)(19)(20)(21)(22)(24)(25)(26) March, and 31 March to 2 April 2019, respectively) were compared. The numerical forecast and SPE data have a 50 × 50 km and~10 × 10 km spatial resolution, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…With respect to extreme precipitation events, Fang et al indicated that although IMERG well captured the spatial pattern of extreme precipitation over China, the topography and climate condition had a significant influence on its performance [24]. In another study, Sunikumar et al demonstrated the ability of IMERG to follow the intraseasonal variability with minor differences observed in the maximum values of precipitation during the rainy season over Japan, Philippines, and Nepal [25]. Mazzoglio et al improved an extreme precipitation detection system using IMERG data and stated that this product guarantees good results when the precipitation aggregation interval is equal to or greater than 12 h [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation